Effects of sensorimotor voice training on event-related potentials to pitch-shifted auditory feedback - Patel, Sona; Hebert, Karen; Korzyukov, Oleg; Larson, Charles R. (PloS one, 2023)
The pitch perturbation technique is a validated technique that has been used for over 30 years to understand how people control their voice. This technique involves altering a person’s voice pitch in real-time while they produce a vowel (commonly, a prolonged /a/ sound). Although post-task changes in the voice have been observed in several studies (e.g., a change in mean f o across the duration of the experiment), the potential for using the pitch perturbation technique as a training tool for voice pitch regulation and/or modification has not been explored. The present study examined changes in event related potentials (ERPs) and voice pitch in three groups of subjects due to altered voice auditory feedback following a brief, four-day training period. Participants in the opposing group were trained to change their voice f o in the opposite direction of a pitch perturbation stimulus. Participants in the following group were trained to change their voice f o in the same direction as the pitch perturbation stimulus. Participants in the non-varying group did not voluntarily change their pitch, but instead were asked to hold their voice constant when they heard pitch perturbations. Results showed that all three types of training affected the ERPs and the voice pitch-shift response from pre-training to post-training (i.e., “hold your voice pitch steady” task; an indicator of voice pitch regulation). Across all training tasks, the N1 and P2 components of the ERPs occurred earlier, and the P2 component of the ERPs occurred with larger amplitude post-training. The voice responses also occurred earlier but with a smaller amplitude following training. These results demonstrate that participation in pitch-shifted auditory feedback tasks even for brief periods of time can modulate the automatic tendency to compensate for alterations in voice pitch feedback and has therapeutic potential.